Genetic associations of psoriasis in a Pakistani population. (13th August 2013) - Shaiq, P.A.; Stuart, P.E.; Latif, A.; Schmotzer, C.; Kazmi, A.H.; Khan, M.S.; Azam, M.; Tejasvi, T.; Voorhees, J.J.; Raja, G.K.; Elder, J.T.; Qamar, R.; et al.
Summary: Background: Genetic predisposition to psoriasis, an inflammatory skin disease affecting 0·2–4% of the world population, is well established. Thus far, 41 psoriasis susceptibility loci reach genome‐wide significance ( P ≤ 5 × 10 −8 ). Identification of genetic susceptibility loci in diverse populations will help understand the underlying biology of psoriasis susceptibility. Objectives: The primary objective of this study was to examine psoriasis susceptibility associations previously reported in Chinese and caucasian populations in a Pakistani cohort. Methods: Blood samples and phenotype data were collected from psoriasis cases and controls in Islamabad, Pakistan. DNA was isolated and genotypes of selected susceptibility markers were determined. The data were analysed using χ 2 tests or logistic regression for psoriasis association. Results: HLA‐Cw6 showed the strongest association [odds ratio (OR) 2·43, P = 2·3 × 10 −12 ]. HLA‐Cw1 showed marginally significant association (OR 1·66, P = 0·049), suggesting that the HLA‐Cw1‐B46 risk haplotype may be present in the Pakistani population. Three other loci ( IL4 / IL13, NOS2, TRAF3IP2 ) showed nominally significant association ( P < 0·05). Conclusions: HLA‐Cw6 is strongly associated with psoriasis susceptibility in the Pakistani population, as has been found in every other population studied. In addition, HLA‐Cw1 showed marginal association, reflecting the relative geographical proximity and thus likely genetic relatedness to other populations in which the HLA‐Cw1‐B46 haplotype is known to be associated. A larger cohort and a denser marker set will be required for further analysis of psoriasis associations in the South Asian population. Abstract : What's already known about this topic? Psoriasis is an autoimmune disease with 41 known genetic loci of genome‐wide significance. All of these loci have been identified in European caucasian or Chinese populations. What does this study add? Analysis of this Pakistani cohort showed genome‐wide significant association for HLA‐Cw6, and nominal significance for three other loci. This study also found nominally significant association with HLA‐Cw1, an association not previously observed outside Thailand and Japan.